HUMAN/MACHINE: THE FUTURE OF OUR PARTNERSHIP WITH MACHINES - Anuncius Gumawang Jati (Jurnal Sosioteknologi, 2020)
In the past ten years, the mainstream media suggests that we should worry that smart machines might steal away specific jobs. If the case is about millions of jobless due to smart machines which are capable of carrying out cheaper and more efficient tasks, this has increased the list of 21st century fears. It is worth remembering that the process itself goes back a long way. I feel a little